Predictors for sentinel lymph node mapping failure using indocyanine green injection in apparent early stages of endometrial cancer: A single-center prospective study - Bretová, Petra; Minář, Luboš; Ovesná, Petra; Weinberger, Vít; Felsinger, Michal; Koblížková, Michaela; Hausnerová, Jitka; Jandáková, Eva; Stupková, Tatiana (International journal of gynaecology and obstetrics: the official organ of the International Federation of Gynaecology and Obstetrics, 2025)
OBJECTIVE: The current study aimed to analyze predictive factors of sentinel lymph node mapping failure in apparently early stages of endometrial cancer using intracervical indocyanine green injection. METHODS: A single-center prospective study was conducted between June 2019 and August 2023 at the Department of Gynecology and Obstetrics, University Hospital Brno, Czech Republic. All patients with apparently early stage (I or II according to FIGO [International Federation of Gynecology & Obstetrics] 2009) endometrial cancer, who were indicated for sentinel node biopsy were consecutively included. The injection of 4-6 mL of indocyanine green was applied superficially and deeply into cervical tissue at the 3- and 9-o'clock positions. Patients' clinical data, surgical characteristics, and histopathological information were recorded. Univariable and multivariable regression analyses were applied. RESULTS: A total of 225 patients were eligible during the study period. Considering bilateral and unilateral failed mapping together, the only statistically significant factors for risk of failure in univariable analysis were body mass index (BMI; P = 0.036), FIGO 2009 stage (P = 0.019), and the presence of a myoma (P = 0.017). Nevertheless, when the multivariable logistic regression analysis was applied, all factors became statistically insignificant except for myoma (P = 0.031). Regarding only bilateral mapping failure, in univariable analysis, BMI (P = 0.021) and FIGO 2009 stage (P = 0.046) were significant predictors of failure. Interestingly, multivariable logistic regression analysis revealed that in addition to BMI (P = 0.007), age (P = 0.004) was also an independent predictor of bilateral failure. CONCLUSIONS: Higher BMI and age were statistically significant independent factors for bilateral sentinel node mapping failure in early-stage endometrial cancer.
Keywords: Neoplasm Staging; lidé; Middle Aged; Adult; Risk Factors; lymfatické metastázy; prospektivní studie; Female; indokyanová zeleň; Body Mass Index; Humans; staging nádorů; index tělesné hmotnosti; barvicí látky; Prospective Studies; Indocyanine Green; sentinel lymph node; Česká republika; lidé středního věku; endometrial cancer; biopsy; obesity; Lymphatic Metastasis; Sentinel Lymph Node Biopsy; Coloring Agents; Czech Republic; ženské pohlaví; nádory endometria; Sentinel Lymph Node; biopsie sentinelové lymfatické uzliny; Aged; Endometrial Neoplasms; myomas; dospělí; sentinelová uzlina; rizikové faktory; senioři